(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Insufficient nurse staffing levels are associated with missed nursing care and negative patient outcomes. Inadequate staffing leads to task omissions by nurses, resulting in diminished care quality, reduced patient safety, and increased mortality rates. This conflict between patient care and professional standards can result in job dissatisfaction and staff turnover. This research delves into the perspectives and experiences of healthcare professionals and patients regarding nurse staffing levels and their effects on patient safety and care quality within hospital environments. Findings indicated that participants highly prioritize timely and appropriate care from nurses, effective nurse-patient communication, and overall patient satisfaction, all of which are closely tied to adequate nurse staffing levels. Concerns were raised regarding the potential negative consequences of nurse-patient ratios and staffing deficiencies on treatment quality, as well as on the workload and stress levels of healthcare staff. The results underscore the critical role of nurse staffing in fostering a safe and supportive healthcare environment. Nonetheless, apprehensions surrounding nurse-patient ratios and staffing deficits call for further exploration. Future research should delve into the factors contributing to staffing shortages, diverse cultural perspectives, and cost-effectiveness considerations.